الاختلافات الاجتماعية في رواية باميلا لــ : صموئيل ريتشاردسون؛ أو الفضيلة المكافأة عليها والآمال العظيمة لــ : تشارلز ديكنز - AbdAlhfed, Salah Faraj; Omar, Hanan Masaud (Al-Qurtas, 2025)
Different social classes exist because different individuals have varying obligations and entitlements in their social lives. It means that rich people who can complete many rights and obligations will be classified as upper-class citizens. Those who possess few or none of these traits will be classified as belonging to the lower classes. Therefore, this study aims to explain the phenomenon of diverse social classes in Pamela and Great Expectations, as well as the socioeconomic conditions of 18th- and 19th-century England. The study examines the information in the two literary works associated with the research issue. According to this study’s findings, during the Victorian era in England, social bias in the community became a big concern. In this civilization, a person’s social position has become the defining factor for interacting with others. The circumstances of a person’s birth have an outsized effect on his or her prospects of achieving success and obtaining respect.